Assessment of ERA5-Land Reanalysis Precipitation Data in the Qilian Mountains of China - Lihui Qian; Peng Zhao (Atmosphere)
Precipitation serves as a crucial indicator of climate change and a vital part of the water cycle in mountainous regions. ERA5-Land, a cutting-edge global reanalysis dataset designed for land applications, has been extensively utilized in climate-related studies. In this research, we assessed the reliability of ERA5-Land monthly averaged reanalysis precipitation data in the Qilian Mountains (QLM). We did this by comparing it with the observations from 17 meteorological stations spanning from 1979 to 2017. The findings indicated that, overall, the ERA5-Land reanalysis precipitation data tended to overestimate the observed precipitation in the Qilian Mountains. The determination coefficient (R2) of the linear regression between ERA5-Land reanalysis precipitation and the observations was 0.97. This value implies that ERA5-Land reanalysis precipitation generally has good applicability in the Qilian Mountains. However, the annual-scale root mean square error (RMSE) was 3.97. This suggests that ERA5-Land reanalysis precipitation data cannot be directly applied to studies at a single meteorological station. The deviation between the ERA5-Land reanalysis precipitation data and the observed precipitation data can be ascribed to the altitude difference between meteorological stations and ERA5-Land grid points. Generally, as the altitude difference between meteorological stations and ERA5-Land grid points increases, the precipitation deviation also rises. This research can furnish a reference for the application of ERA5-Land reanalysis precipitation data in the Qilian Mountains.